The measurement of microbial air contamination index in the pulmonary ward, intensive care unit and pediatric intensive care unit at dr. Zainoel Abidin hospital, Aceh, Indonesia - RINANDA, TRISTIA; SAKDIAH, SAKDIAH; RISTIANTI, RIMA; YUNIRA, VONNA; VANIA, FEBY; BUANA, ANDIKA CITRA (Jurnal Natural, 2025)
Nosocomial infections are one of the major problems in hospitals. Air is one source of nosocomial infections. Hospitals are filled with many patients, their families, and health workers daily. This large number of people allows the spread of various microorganisms through the air in droplets dispersed through breathing, talking, coughing or sneezing. This study used passive air sampling or settle plate method to measure the air quality in the pulmonary ward, Intensive Care Unit (ICU) and Pediatric Intensive Care Unit (PICU) at dr. Zainoel Abidin Hospital (RSUDZA). The air microbial contamination index was determined by counting the microbial colonies grown on Nutrient Agar and converted to CFU/m3 of air volume using the Polish Standard PN 89/Z-04008/08 Formula. The results showed that the air microbial contamination index in the pulmonary ward, ICU and PICU exceeded the maximum threshold mentioned in the decree of the Minister of Health of the Republic of Indonesia No.1204/SK/X/2004, which was 500 CFU/m3 for the pulmonary ward and 200 CFU/m3 for the Intensive Care Units. Although the findings of this study only represent the large microbial particles pulled by gravity, the high microbial contamination index of each unit trigger air quality alerts. Therefore, adequate air system management and periodic monitoring are needed to improve air quality in the wards and intensive care units at RSUDZA.